2022
DOI: 10.1093/bjs/znac193
|View full text |Cite
|
Sign up to set email alerts
|

Association of Upper Gastrointestinal Surgery of Great Britain and Ireland (AUGIS)/Perioperative Quality Initiative (POQI) consensus statement on intraoperative and postoperative interventions to reduce pulmonary complications after oesophagectomy

Abstract: Background Pulmonary complications are the most common morbidity after oesophagectomy, contributing to mortality and prolonged postoperative recovery, and have a negative impact on health-related quality of life. A variety of single or bundled interventions in the perioperative setting have been developed to reduce the incidence of pulmonary complications. Significant variation in practice exists across the UK. The aim of this modified Delphi consensus was to deliver clear evidence-based cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Previous studies showed that perioperative interventions, including protective ventilation strategy [18,19], high-ow nasal cannula [20], epidural analgesia and regional anesthesias [21], respiratory physiotherapy [22,23], can reduce PPCs and improve oxygenation with thoracic and abdominal surgery. However, no high-quality evidence was found for interventions to reduce incidence of PPCs [24,25]. An intraoperative mechanical ventilation strategy with a higher level of PEEP and recruitment maneuvers did not reduce PPCs and protect postoperative spirometry in noncardiac surgery [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that perioperative interventions, including protective ventilation strategy [18,19], high-ow nasal cannula [20], epidural analgesia and regional anesthesias [21], respiratory physiotherapy [22,23], can reduce PPCs and improve oxygenation with thoracic and abdominal surgery. However, no high-quality evidence was found for interventions to reduce incidence of PPCs [24,25]. An intraoperative mechanical ventilation strategy with a higher level of PEEP and recruitment maneuvers did not reduce PPCs and protect postoperative spirometry in noncardiac surgery [26][27][28].…”
Section: Discussionmentioning
confidence: 99%